Belk's (1988) "Possessions and the extended self" revisited. (18th May 2015) - Ladik, Daniel; Carrillat, Francois; Tadajewski, Mark
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to revisit Russell Belk's (1988) landmark paper "Possessions and the extended self". The authors provide a prehistory of related ideas and then examine the controversy it triggered regarding the different paradigms of research in marketing (Cohen, 1989) some 26 years ago. Design/methodology/approach – This paper takes Belk seriously when he argues that his work is a synthesis and extension of prior studies leading to the novel production of the "extended self" concept. Via a close reading of the history of self-constitution, the authors highlight a number of thinkers who were grappling with similar issues now associated in our disciplinary consciousness to the idea of the "extended self". To assess the contribution of Belk's work, the authors engage in citation and interpretive analyses. The first analysis compared scholarly citations of Belk (1988) with the top ten most-cited Journal of Consumer Research (JCR) papers published in the same year. The second citation analysis compared Belk (1988) to the top ten most-cited JCR papers in the history of the journal. The authors follow this with an interpretive analysis of Belk's contribution to consumer research via his 1988 paper. Findings – Belk (1988) had the most citations (N = 934) of any paper published in JCR in 1988. When compared to all papers published in the history of JCR, Belk (1988) leads with the most overall citations. Moreover, Belk (1988) is the most prominent interpretive paper that appeared in JCR and one of the top three, regardless of paradigm. The analysis illustrates diversity in topic and methodology, thus indicating that Belk's contribution impacted a wide variety of scholars. Interpretive analysis indicates the importance of Belk's work for subsequently impactful consumer researchers. Originality/value – The authors offer a prehistory of the "extended self" concept by highlighting literature that many consumer researchers will not have explored previously. With citations spanning over three decades, consumer behavior scholars recognize Belk (1988) as an important paper. Our analysis reveals that contrary to received wisdom, it is not only important for interpretive researchers or scholars within the consumer culture theory, but it is significant for the entire discipline, irrespective of paradigmatic orientation. The research presented here demonstrates that Belk's (1988) paper is arguably one of the most influential papers ever published in JCR.